SCN1A IVS5N+5 polymorphism and response to sodium valproate: a multicenter study - Haerian, B.S.; Baum, L.; Tan, H.J.; Kwan, P.; Raymond, A.A.; Saruwatari, J.; Nakagawa, K.; Mohamed, Z. (2012)
Aim: Approximately 30 of epilepsy patients do not response to antiepileptic drugs (AEDs). The functional SCN1A IVS5N+5 polymorphism may play a role in response to some AEDs. The purpose of this study was to examine this hypothesis in a cohort study of Malaysian and Hong Kong Chinese epilepsy patients on sodium valproate (VPA) monotherapy and in a meta-analysis. Patients & methods: The SCN1A IVS5N+5 polymorphism was genotyped in 583 Malaysian (84) and Hong Kong Chinese (16) epilepsy patients receiving VPA monotherapy. The related association studies, including the current study, were meta-analyzed by using fixed- and random-effects models under various genetic models. Results: A total of 277 (47.5) and 306 (52.5) patients were VPA nonresponsive and responsive, respectively. Unlike Chinese and Indian patients, Malay nonresponsive patients with idiopathic generalized epilepsy showed significant association, probably caused by the small sample size. Conclusion: The cohort study and meta-analysis did not demonstrate an association between AED responsiveness and this polymorphism. Future studies with a larger sample size of Malays with idiopathic generalized epilepsy are suggested. Original submitted 15 June 2012; Revision submitted 23 July 201. Â© 2012 Future Medicine Ltd.